1993
DOI: 10.1523/jneurosci.13-05-02230.1993
|View full text |Cite
|
Sign up to set email alerts
|

Short-term changes in the numerical density of synapses in the intermediate and medial hyperstriatum ventrale following one-trial passive avoidance training in the chick

Abstract: Previous ultrastructural studies using stereological counting techniques, based on assumptions regarding shape, size, and orientation of synapses, have suggested synaptic remodeling occurred at least 24 hr after one-trial passive avoidance training in day-old chicks. The present study estimates the mean synaptic density (Nv syn) in a region of the chick forebrain known to be involved in memory formation, the intermediate and medial hyperstriatum ventrale (IMHV), 1 and 24 hr following one-trial passive avoidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 33 publications
2
24
1
Order By: Relevance
“…Studies, which have tested the visual discrimination in the chick, have consistently shown the importance of the right eye and the left hemisphere pathway in acquisition of such tasks (Rogers, 1986). The results presented here in which the left hemisphere has a superiority to the right hemisphere in terms of increase in N V syn after training in certain illumination colors are consistent with the idea of the importance of the left hemisphere in visual discrimination learning (Gasten and Gasten, 1984;Rogers, 1986;Patel and Stewart, 1988;Doubell and Stewart, 1993).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Studies, which have tested the visual discrimination in the chick, have consistently shown the importance of the right eye and the left hemisphere pathway in acquisition of such tasks (Rogers, 1986). The results presented here in which the left hemisphere has a superiority to the right hemisphere in terms of increase in N V syn after training in certain illumination colors are consistent with the idea of the importance of the left hemisphere in visual discrimination learning (Gasten and Gasten, 1984;Rogers, 1986;Patel and Stewart, 1988;Doubell and Stewart, 1993).…”
Section: Discussionsupporting
confidence: 87%
“…Clearly an increase or a decrease in N V syn may not reflect an increase or a decrease in number of synapses if the reference volume decreases or increases by a relevant amount. It was reported that after 24 hr passive avoidance training no changes occurred in the volume of the lobus parolfactorius (LPO), a region of chick forebrain Hunter (1991) cited by Doubell and Stewart (1993). One day after training, a similar result can be expected for the IMHV (Doubell and Stewart, 1993).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations